DINAMIKA KEBUDAYAAN DAN PERADABAN BATANG KUNA GAMBARAN AWAL BERDASARKAN HASIL EKSPLORASI ARKEOLOGIS - Sugeng Riyanto (BRIN, 2014)
Results of exploratory survey in Batang, Central Java, showing a variety of archaeological data with Hindu-Buddhist influence. There are among others, buildings and building components, inscriptions, statues, phallus-yoni, as well as artifacts that show characteristics of Indian influence. In addition, those various archaeological data obtained from the survey hypothetically reflect the dynamics of ancient Batang culture and civilization which chronologically includes pre-Hindu, the transition from pre-Hindu toHindu, early development of Hindu influence, and the heyday of Ancient Mataram.